Perception vs practice: Farmer attitudes towards and uptake of IPM in Scottish spring barley. (October 2018) - Stetkiewicz, Stacia; Bruce, Ann; Burnett, Fiona J.; Ennos, Richard A.; Topp, Cairistiona F.E.
Abstract: Integrated Pest Management (IPM) offers a suite of ways by which to reduce the need for pesticide use, thus minimising environmental damage and pathogen resistance build-up in crop production. Farmers and agronomists active in the Scottish spring barley sector were surveyed to determine the extent to which they currently use or are open to implementing three IPM measures – varietal disease resistance, crop rotation, and forecasting disease pressure – in order to control three important fungal diseases. Overall, the survey results demonstrate that farmers and agronomists are open to using the three IPM techniques. However, gaps between actual and perceived recent practice were large: despite over 60% of farmers stating that they sowed varieties highly resistant to Rhynchosporium or Ramularia, less than one third of reportedly sown varieties were highly resistant to these diseases. Similarly, over 80% of farmers indicated that they used crop rotations, yet 66% of farmers also reported sowing consecutive barley often/always. Further research is needed in order to understand why these gaps exist, and how they can be reduced in future in order to increase IPM uptake and optimise pesticide use. Highlights: Farmers and agronomists were open to using IPM in Scottish spring barley production. Gaps between actual and perceived practice were large. Most farmers reported sowing highly resistant varieties, yet most reportedly sown varieties were lacking in resistance. Over 80% of farmers indicated that they used crop rotations, yet 66% also sowed consecutive barley often/always.